The Electric Field Calculation for Mobile Communication Coverage in Buildings and Indoor Areas by Using the Method of Auxiliary Sources - Vasil Tabatadze; Kamil Karaçuha; Eldar Veliyev; Ertuğrul Karaçuha; Revaz Zaridze (Complexity)
In this article, the diffraction of the electromagnetic wave by the building with two rooms is considered. The rooms have doors and windows with lossy dielectric walls. The electromagnetic properties of the building as an opened coupled resonator system are investigated at different source locations and several frequencies including 5G band. The problem is solved by using the Method of Auxiliary Sources. The near electric field distributions are calculated and analyzed.